Jurisprudential analysis of Maqasid al-Shariah in managing Mosques funds: a case study of Tabung Masjid (TM) in Malaysia. - Zakariyah, Luqman (2014)

(untitled)
Mosques funds in part of Muslim countries where Tabarruaat (voluntary donation) is in operation ought to have huge impact on Muslim youth empowerment and poverty alleviation. However, managing these funds in these Muslim countries to bring about the foreseen impact remains untapped. In Malaysia, the setup of Tabung Masjid (TM) has not been effective to serve the purpose of Islam. This is either partly due to unawareness of the Islamic jurisprudential perspectives on TM funds or partly due to the uninformed ways to manage these funds. This paper aims to assess way of which funds generated from TM in Malaysian is being managed. Access to the TM management will be sought to evaluate the effectiveness of the impact of these funds. The assessments of the way TM is managed at present will be analyzed on the jurisprudential perspective of Muslim classical and contemporary scholars. The central question of this paper will be how mosques funds can be effectively used for Muslim youth empowerment. The author will suggest, through the analysis of available data of mosques’ funds in Terengganu, Malaysia, productive methods of managing the TM which is more in tandem to the objectives of Islamic Law (Maqasid al-Shariah).